Effect of vaccination in Rabies disease model - Pongsumpun, P. (My University, 2025)
Rabies disease has occurred when the virus enters the body of a person or animal. People or animals infected with this disease have a 100 percent chance of dying. We describe the transmission of this disease by formulating the mathematical model by considering the transmission between human, dog and cat. We found the method to reduce the transmission of rabies disease. The basic reproduction number of disease is found. The parameters to reduce the transmission of disease is found.
Keywords: dynamical modeling method; local stability; Rabies disease; vaccination